Correlates of and barriers to ART adherence among adherence-challenged people living with HIV in southern India - Heylen, Elsa (AIDS Care, 2020)
Suboptimal adherence to Antiretroviral Therapy (ART) regimens can lead to the development of drug resistance, virologic and clinical failure, and, on the community level, the spread of drug-resistant HIV. To design effective interventions, it is crucial to understand locally specific barriers to optimal adherence. Self-report data from a cross-sectional sample of 527 adherence-challenged people living with HIV (PLWH) in the South-Indian state of Karnataka showed that they took on average 68% of prescribed doses in the past month. Large majorities of participants encountered individual (95%), social/structural (88%), and clinic/regimen (80%) adherence barriers. Multivariate linear regression analyses of past month adherence showed that disclosure to all adults in the household was positively related to adherence, as was employing a larger number of adherence strategies, perceiving more benefits of ART, and having been on ART for longer. Fears of stigmatization upon disclosure of HIV-status to friends and people at work were negatively related to adherence. These results suggest that some barriers, especially individual-level barriers like forgetfulness are very common and can be targeted with relatively simple individual-level strategies. Other barriers, related to fear of stigma and lack of disclosure may require family- or community-level interventions.